SHEGARALANǴAN FUNKCIYALARDAN PAYDALANÍP TEŃSIZLIKLERDI SHESHIW USÍLLARÍ - Djumabaev, N. (SCIENCE and SOCIETY, 2017)
The article describes methods of solving nonstandard inequalities using properties of bounded functions.